The motherhood effect on labour market outcomes: evidence from South Korea. (13th October 2022) - Kim, Anna; Hahn, Youjin
Abstract : We examine mothers' relative labour market outcomes around the first childbirth in South Korea, a country with the highest gender pay gaps and the lowest fertility rate among the OECD countries. Using an event study approach, we find that while fathers remain unaffected, mothers' earnings drop sharply by 66.2 per cent over the long run, mostly driven by a reduction in labour force participation. For women who continue to work, motherhood lowers the probability of entering male‐dominated occupations and industries but increases the probability of working in female‐dominated occupations and industries. Finally, we find that motherhood has a stronger negative effect on labour market outcomes for less‐educated mothers, young mothers, mothers who first bear children within two years of marriage, and mothers with three or more children.